2019
DOI: 10.1007/s42380-019-00056-0
|View full text |Cite
|
Sign up to set email alerts
|

Victimization Experiences and Mental Health Outcomes Among Grades 7 to 12 Students in Manitoba, Canada

Abstract: Victimization experiences, including traditional forms of bullying, discriminatory harassment, and cyber victimization, are associated with numerous detrimental consequences in adolescence and over the life course. The objective of the current study was to understand the relationships between nine experiences of victimization and mental health outcomes among students in grades 7 to 12 in Manitoba, Canada. Data were drawn from the 2012-2013 Manitoba Youth Health Survey (N = 64,174; response rate = 67%). Mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…Educators and public health officials working on such programs need to be aware of increased likelihood of substance use among adolescents who experience victimization. Traditional bullying prevention programs need to consider the mounting evidence that victimization experiences that fall just beyond the traditional definition of bullying are also associated with poor outcomes (Stewart-Tufescu et al 2019;Turner et al 2018). This study supports other calls for crosscurricular programs addressing both substance use and bullying/victimization to better support the healthy (Hirschtritt 2020).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Educators and public health officials working on such programs need to be aware of increased likelihood of substance use among adolescents who experience victimization. Traditional bullying prevention programs need to consider the mounting evidence that victimization experiences that fall just beyond the traditional definition of bullying are also associated with poor outcomes (Stewart-Tufescu et al 2019;Turner et al 2018). This study supports other calls for crosscurricular programs addressing both substance use and bullying/victimization to better support the healthy (Hirschtritt 2020).…”
Section: Discussionsupporting
confidence: 77%
“…However, adolescents also experience victimization outside of traditionally defined bullying such as single interactions of cyber-victimization and discriminatory harassment (Salmon et al 2018). Additionally, single exposures to specific victimization experiences have been associated with moderate/languishing mental health functioning and emotional well-being among adolescents (Stewart-Tufescu et al 2019). Bullying has been associated with risk taking behaviours such as drinking alcohol and smoking (Quinn et al 2016a, b;Vieno et al 2011) so it may also be possible that associations between single exposure victimization experiences and substance use such as binge drinking and smoking may also exist.…”
mentioning
confidence: 99%
“…Previous research has found that boys compared to girls are more likely to use substances (Bava & Tapert, 2010). Importantly, recent work has also indicated that girls with a peer victimization history were found to have greater odds of poor health outcomes and increased feelings of sadness and hopelessness (Stewart-Tufescu et al, 2021). It is possible that girls are more likely to use substances as a way to cope.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, helplessness may affect adolescent physical health, mental health, and well-being. 15 , 16 , 17 , 18 , 19 However, some adolescents can catalyze their emotions and transform them into action.…”
Section: Discussionmentioning
confidence: 99%